2019
DOI: 10.21608/mjcu.2019.52521
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes Induced by Potassium Dichromate in Renal Cortex of Adult Male Albino Rats and the Possible Protective Role of Selenium

Abstract: Background: Potassium Dichromate (Cr) is a common environmental agent that has been considered potentially carcinogenic, making it an issue of major environmental and search concern. Aim of Study: The aim of this study was to throw light on the possible structural changes in the renal cortex of adult male albino rats after administration of Cr and to elucidate the possibility of protection by selenium (Se) against the deleterious effects of Cr. Material and Methods: Thirty six adult male albino rats weighing 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The renal cortex had enlarged renal corpuscles with a wide renal space, tubular degeneration, and proximal convoluted tubules which displayed vacuolar degeneration with a luminal cast, and distal convoluted tubules which showed the complete loss in the cytoplasmic content with the sloughing of the lining cuboidal cells into the tubular lumen. These findings are in accordance with previous reports [ 65 , 66 , 67 ], which were suggestive that K 2 Cr 2 O 7 -induced toxicity and the induction of oxidative stress and apoptosis arise through the generation of reactive oxygen species (ROS). Consequently, ROS triggered K 2 Cr 2 O 7 toxicity owing to the reduction of hexavalent chromium to the trivalent form, thereby inducing damage to the cellular components [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…The renal cortex had enlarged renal corpuscles with a wide renal space, tubular degeneration, and proximal convoluted tubules which displayed vacuolar degeneration with a luminal cast, and distal convoluted tubules which showed the complete loss in the cytoplasmic content with the sloughing of the lining cuboidal cells into the tubular lumen. These findings are in accordance with previous reports [ 65 , 66 , 67 ], which were suggestive that K 2 Cr 2 O 7 -induced toxicity and the induction of oxidative stress and apoptosis arise through the generation of reactive oxygen species (ROS). Consequently, ROS triggered K 2 Cr 2 O 7 toxicity owing to the reduction of hexavalent chromium to the trivalent form, thereby inducing damage to the cellular components [ 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…The current study revealed little collagen fibers in the cortical interstitium around the renal corpuscles and tubules in Masson's trichrome stained specimens of protected groups. The results agreed with Ahmed et al, (2019) [45] . The (PFOS) administered group in the present study exhibited significant increase of iNOS immunohistochemical reaction.…”
Section: Discussionsupporting
confidence: 92%
“…They also stated that the treated animals showed intraluminal and intracytoplamic accumulation of acidophilic hyaline and renal cast content (Hegazy et al, 2016). Also other studies showed similar findings (El-Mahalaway et al, 2015;Hanan et al, 2019).…”
Section: Discussionmentioning
confidence: 72%